Sejarah Perkembangan Hukum Agraria di Indonesia Sebelum Dibentuknya Undang-Undang No. 5 Tahun 1960 Tentang Peraturan Dasar Pokok-Pokok Agraria (UUPA) Dan Dampaknya Bagi Keadilan Di Masyarakat - Muhammad Abdussalam Rafie; Willson Chandra Happier (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Agrarian law has a fairly high position in Indonesia. This is because there are so many problems in Indonesia that have a relationship with the existence of the territory of the Indonesian state. This is also increasingly influenced by the layout of the Indonesian state which is an agrarian country. This then led to the importance of strengthening the law relating to agrarian issues in Indonesia. This research then aims to be able to see how the development of agrarian law, especially agrarian law in Indonesia. This research will be carried out using a normative juridical approach that focuses on the study of literature and laws that are still related to the realization of justice in the agrarian sector in Indonesia. The results of this study found that there were many long-standing problems regarding agrarian law since the colonial era until after independence. Policies made by the government must have a firm nature when dealing with various land mafias. In the process, the government needs to provide good services regarding various programs that have been made, such as land certification, and provide legal supervision based on social justice for the community so as not to cause agrarian conflicts.